Internet Freedom and Political Space - Tkacheva, Olesya; Schwartz, Lowell H.; Libicki, Martin C.; Taylor, Julie E.; Martini, Jeffrey (RAND Corporation, 2023)
The Internet is a new battleground between governments that censor online content and those who advocate freedom for all to browse, post, and share information online. This report examines how Internet freedom may transform state-society relations in nondemocratic regimes, using case studies of China, Egypt, Russia, and Syria, and also draws parallels between Internet freedom and Radio Free Europe programs during the Cold War.